2017
DOI: 10.1074/jbc.m117.803445
|View full text |Cite
|
Sign up to set email alerts
|

BNGR-A25L and -A27 are two functional G protein–coupled receptors for CAPA periviscerokinin neuropeptides in the silkworm Bombyx mori

Abstract: CAPA peptides, such as periviscerokinin (PVK), are insect neuropeptides involved in many signaling pathways controlling, for example, metabolism, behavior, and reproduction. They are present in a large number of insects and, together with their cognate receptors, are important for research into approaches for improving insect control. However, the CAPA receptors in the silkworm () insect model are unknown. Here, we cloned cDNAs of two putative CAPA peptide receptor genes, BNGR-A27 and -A25, from the brain of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
(44 reference statements)
2
4
0
Order By: Relevance
“…Aedae -PK1 is a member of the pyrokinin-1 family of peptides that contain the GXWFGPRL-NH 2 (where normally X = V, M or L) consensus C-terminal sequence and recently a revised tryptopyrokinin nomenclature has been adopted to differentiate these neuropeptides from distinct pyrokinin families 88 . In agreement with our findings, a subset of previous studies on insect CAPA receptor orthologs have shown minor responsiveness to tryptopyrokinin ligands, with high doses eliciting low level CAPA receptor activation 8486 . Interestingly, this minor promiscuousness has not been observed for other dipteran CAPA receptors characterized previously 57,82,83 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Aedae -PK1 is a member of the pyrokinin-1 family of peptides that contain the GXWFGPRL-NH 2 (where normally X = V, M or L) consensus C-terminal sequence and recently a revised tryptopyrokinin nomenclature has been adopted to differentiate these neuropeptides from distinct pyrokinin families 88 . In agreement with our findings, a subset of previous studies on insect CAPA receptor orthologs have shown minor responsiveness to tryptopyrokinin ligands, with high doses eliciting low level CAPA receptor activation 8486 . Interestingly, this minor promiscuousness has not been observed for other dipteran CAPA receptors characterized previously 57,82,83 .…”
Section: Discussionsupporting
confidence: 93%
“…The current study provides definitive evidence supporting the importance of this anti-diuretic hormone system in the disease vector mosquito, A. aegypti , by characterization and functional deorphanization of an anti-diuretic hormone receptor that is highly enriched in the MTs and demonstrates high selectivity for the mosquito CAPA neuropeptides. Previous studies have functionally deorphanized a number of CAPA receptor orthologs in other insects including dipterans 44,57,82,83 , lepidopterans 84 , coleopterans 85 , hemipterans 86 , as well as in the southern cattle tick 87 . Here, we have functionally validated the specific ligands of the elusive A. aegypti CAPA receptor demonstrating that two of the peptides encoded by the mosquito CAPA gene 50 , Aedae -CAPA1 and –CAPA2, potently activate this receptor leading to calcium signalling that elicits a bioluminescent response.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of an orphan GPCR with a given neuropeptide is a first and also the key step to fully understand its signaling and actions. The silkworm, B. mori , belonging to the larger Lepidopteran insects, is an important domesticated insect due to its role in silk production, and also severs as one of the best characterized models for insect biochemical, genetic, and genomic studies 25,27 . However, despite its great value, basic research focused on GPCRs in this insect has lagged far behind other model organisms such as D. melanogaster and C. elegans .…”
Section: Discussionmentioning
confidence: 99%
“…The pCRE‐luciferase (Luc) was performed to investigate the intracellular levels of cAMP as a reporter gene system that contains the cAMP‐response elements and firefly luciferase coding region as described before 27 . Cells co‐expressing Bombyx receptors or empty vector as control with pCRE‐Luc were grown to 90%–95% confluence in 96‐well plates and stimulated with different Bombyx neuropeptides in DMEM without FBS for 4–6 h at 37°C (HEK293T) or 27°C (Sf9).…”
Section: Methodsmentioning
confidence: 99%
“…The rhodopsin-like family A GPCR for CAPA has been characterized in D. melanogaster (CG14575), A. gambiae, R. prolixus, B. mori, and predicted in several other species (68). The GPCRs are evolutionarily related to vertebrate neuromedin receptors.…”
Section: Capa and Its Receptormentioning
confidence: 99%